PENGARUH PENDIDIKAN PONDOK PESANTREN TERHADAP AKHLAK PESERTA DIDIK DI TASIKMALAYA - Rosmiati, Santi; Suhrowardi, Suhrowardi; Hasani, Syarief (THORIQOTUNA: Jurnal Pendidikan Islam, 2019)
This study aims to determine the effect of boarding schooleducation on morals students of class XII Madrasah Aliyah Negeri 3Tasikmalaya. Based on the results of data processing obtained theEffect of boarding school education is quite. It is based on the results ofresearch conducted to 34 respondents using a questionnaire, That is theinfluence of a high between of boarding school education on moralslearners in the school. Through hypothesis testing it is stated that thereis positive influence between two variables is accepted. Past resultscalculate the coefficient of determination is known that there isinfluence by 38%, rest influenced by other factors, which amounted to62%. Thus, it turns out that there are many factors that influence themorality of students.